Sistem Informasi Pajak Reklame Menerapkan Metode Prototype - Anisyah Dinda Mawadha; Suyanto Suyanto (STMIK Budi Darma, 2023)
The Advertising Tax Information System is a system developed to assist the Palembang City Regional Tax Management Agency in managing advertisement tax data and information. This study aims to overcome the problems that exist in the current advertisement tax management system, where the advertisement tax payment process is still manual and inefficient, and difficulties in tracking advertisement tax payments and ensuring that all payments are made on time, therefore it takes a system that can control it all using information technology. Through this system, billboard tax payments can be made online and tax data can be managed more efficiently and accurately. This research uses a system development method using a prototype and is complemented by system analysis and design. The result of this research is a billboard tax information system that is able to simplify the payment process and tax data management, and has succeeded in increasing the accuracy of billboard tax data by 25%, from 80% to 95%. This system is expected to provide benefits for the Palembang City Regional Tax Management Agency and taxpayers in terms of time and cost efficiency which can make it easier for taxpayers, admins, and leaders to properly carry out registration, reporting, extension, and closing advertisement taxes